The Effect of Instruction of Islamic life Skills on Self-regulation Learning Strategies, Identity Styles and Development of Moral Sense in Students - Reza Norouzi-Kouhdasht; Mohammad Jafar Mahdian; Ali Babaei; Kobra Raoufi; Zeinab Rajabzadeh; Marzieh Karamkhani (Shahid Beheshti University of Medical Sciences, 2020)
For downloading the full-text of this article please click here. Background and Objective: Islamic life skills are the abilities that develop by emphasizing religious instructions and continuous practice, prepare adolescents for encountering life problems and increase their social and mental abilities and skills. Accordingly, the need for interventions at the education level to prevent social harms is more highly felt. The present study examined the effect of instruction of Islamic life skills on self-regulation learning strategies, identity styles and development of moral sense in students. Methods: This was an interventional study involving a clinical trial in which a quasi-experimental pretest-posttest design was used. The statistical population included all the high school students in male-only schools in the first grade in region 22 of Tehran, who were selected using multi-stage cluster sampling and out of which Shahid Motahhari School was randomly selected. Forty students were selected from this school using accessible sampling, who were assigned to experimental (n=20) and control (n=20) groups. The former received eight weekly sessions of intervention in the form of instruction of Islamic life skills. The data collection instruments included Motivated Strategies for Learning Questionnaire (MSLQ), Identity Styles Questionnaire (6G-ISI) and Defining Issues Test (DIT). The collected data was analyzed using covariance analysis. In this study, all the ethical considerations were observed and the authors reported to conflicts of interest. Results: Based on the findings, instruction of Islamic life skills caused improved scores in self-regulation learning strategies (metacognitive=0.27 and cognitive=0.59). It also led to changes in normative identity (0.43) and commitment (0.76). Instruction of life skills accounted for 37% of the variance in students' development of moral sense. Conclusion: Instruction of Islamic life skills enables students to develop an independent identity as a pious adolescent committed to religious values, develop their ability to define issues, improve their self-regulation learning strategies and change their knowledge, values and opinions into real abilities.For downloading the full-text of this article please click here. Please cite this article as: Norouzi-Kouhdasht R, Mahdian MJ, Babaei A, Raoufi K, Rajabzadeh Z, Karamkhani M. The Effect of Instruction of Islamic life Skills on Self-regulation Learning Strategies, Identity Styles and Development of Moral Sense in Students. Journal of Pizhūhish dar dīn va salāmat. 2020;6(1):116-130. https://doi.org/10.22037/jrrh.v6i1.18153